PENGEMBANGAN MODUL MATERI STATISTIK BERBASIS PENDEKATAN PMR BAGI SISWA SMK KELAS XI - Uki Suhendar (Universitas Muhammadiyah Ponorogo, 2016)
This research kind is a research and development. The purpose of this research is to produce module statistical material based PMR-approach for Class XI student of SMK valid, practical, and effective. The developmental research refers to the model ADDIE with the stages of analysis, design, development, implementation, and evaluation. The field testing subjects is 15 students of class XI of SMK Brawijaya Ponorogo. The data were collected using an sheet module validation, achievement test and questionnaire practicality. The data were analyzed using the analysis of the mean scores and descriptive statistics. The results of this research are summarized valid module with revision. The module is said to be effective based on the results of tests on 15 students with the result that students who meet the criteria of the increase amounted to 86.67%. Modules are also said to be practically based questionnaire practicality filled teacher then analyzed and obtained a mean score of 4.60 or on the criteria very well.Keywords: module, PMR, statistical